Co-Targeting Tumor Angiogenesis and Immunosuppressive Tumor Microenvironment: A Perspective in Ethnopharmacology - Zhou, Jianbo; Wang, Li; Peng, Cheng; Peng, Fu (Frontiers in Pharmacology, 2022)
Tumor angiogenesis is one of the most important processes of cancer deterioration via nurturing an immunosuppressive tumor environment (TME). Targeting tumor angiogenesis has been widely accepted as a cancer intervention approach, which is also synergistically associated with immune therapy. However, drug resistance is the biggest challenge of anti-angiogenesis therapy, which affects the outcomes of anti-angiogeneic agents, and even combined with immunotherapy. Here, emerging targets and representative candidate molecules from ethnopharmacology (including traditional Chinese medicine, TCM) have been focused, and they have been proved to regulate tumor angiogenesis. Further investigations on derivatives and delivery systems of these molecules will provide a comprehensive landscape in preclinical studies. More importantly, the molecule library of ethnopharmacology meets the viability for targeting angiogenesis and TME simultaneously, which is attributed to the pleiotropy of pro-angiogenic factors (such as VEGF) toward cancer cells, endothelial cells, and immune cells. We primarily shed light on the potentiality of ethnopharmacology against tumor angiogenesis, particularly TCM. More research studies concerning the crosstalk between angiogenesis and TME remodeling from the perspective of botanical medicine are awaited.